Proceso de atención de enfermería aplicado a la salud escolar de niños/as de 4to Año de Educación Básica Paralelo B de la Escuela Fiscal Mixta Julio María Matovell - Carrión Armijos, Jéssica Beatriz (2014)
The school district Julio María Matovelle The band located north of the city of Loja has a student population 498 boys / girls , within which this research work the same as main objective was made " Apply Process Of Attention Applied to nursing School Health of Children From the 4th Paralelo Year Basic Education "B" De La Escuela Fiscal Mixta Julio María Matovelle , interrelacionándolo codes with NANDA , NIC, NOC . The study was conducted in the research field of descriptive cross rate, taking as sample 29 schools , to which we applied a tool to gather information which in turn was supplemented with information provided by the representatives or parents family of children through home visits and observation of the home environment. Pattern No.2 Nutrition - Metabolic presence of dental caries , pattern No. 7 Self- Management and Self-concept and self-rated health , with flag affected self-medication - as a result the pattern No. 1 was found altered perception , shown little capacity to adapt and indecisive behavior; pattern No. 10 Vital Principles in the revelation which has behavior and isolation. After obtaining the results , efforts to help resolve the problems found through actions that impact the school community and develop an individualized story time , which remained as a record in the institution were raised. Keywords: Process, care, nursing, health, school.